Recurrent outbreaks caused by the same Salmonella enterica serovar Infantis clone in a German rehabilitation oncology clinic from 2002 to 2009. Issue 4 (December 2018) - Miller, T.; Brockmann, S.; Spackova, M.; Wetzig, J.; Frank, C.; Pfeifer, Y.; Braun, P.G.; Prager, R.; Rabsch, W.
Summary: Background: Repeated outbreaks of salmonellosis caused by Salmonella enterica serovar Infantis at a rehabilitation clinic in Germany were investigated microbiologically from August 2002 to August 2009. Aim: To identify the sources of transmission and characterize the S. enterica serovar Infantis isolates. Methods: Associated with these outbreaks, isolates from 98 patients, two kitchen staff, five food samples, four swabs of kitchen facilities, three samples of chicken faeces and one sample of sewage water were evaluated by phage typing. All S. enterica serovar Infantis isolates investigated ( N =113) were related to phage type (PT) 29. Additionally, 44 of the 113 isolates were selected at random for typing by XbaI macrorestriction and pulsed-field gel electrophoresis (PFGE). Findings: Typing of the 44 isolates showed that the recurrent infections were caused by the single clone PT 29/XB27+44 (42/44, 95.5%). The most likely route of transmission was only identified in the last outbreak in 2009 within the present study. It was found to be cross-contamination in the kitchen facilities (emanating from a contaminated wooden panel), in combination with carriers among the kitchen staff. Conclusions: This study demonstrated important details of hospital-specific epidemiological processes, and alludes to a long-term reservoir of an epidemic clone of S. enterica serovar Infantis either in a backyard flock of poultry or in an inanimate kitchen reservoir.